MANAJEMEN SERTA FUNGSI ZAKAT PADA BADAN AMIL ZAKAT DAN LEMBAGA AMIL ZAKAT - Susila, Ahdiyat Agus (Finance : Journal of Accounting and Finance, 2023)
Zakat is a specific portion of wealth that must be given by every Muslim once certain conditions are met. As one of the five pillars of Islam, zakat holds a fundamental place in the life of a Muslim, serving as a means of redistributing wealth to those who are entitled to receive it (mustahik). One of the most well-known obligatory forms of zakat is zakat fitrah, which is paid annually during the month of Ramadan as a way to purify the soul before Eid al-Fitr. In Indonesia, zakat fitrah is typically paid in the form of 3.5 liters of staple food, usually rice, based on local consumption patterns. Besides zakat fitrah, there are several other types of zakat, each with its own rules and guidelines, including: (1) Zakat Fitrah, (2) Zakat on Wealth (Zakat Mal), (3) Zakat on Gold and Silver, (4) Zakat on Livestock, and (5) Zakat on Trade (Tijarah). Given the complexity and diversity of zakat types in Indonesia, managing zakat effectively cannot be handled individually. It requires structured institutions capable of collecting and distributing zakat properly and transparently. This study aims to explore the management of zakat by Badan Amil Zakat (BAZ) and Lembaga Amil Zakat (LAZ), especially regarding how zakat is collected and distributed to eligible recipients. A qualitative approach was used in this research to gain a deeper understanding of effective zakat management practices. The findings of this study are expected to contribute to the development of a more accountable and efficient zakat management system in Indonesia. Key components discussed in this research include: (a) the research topic, (b) objectives, (c) research methodology, (d) research findings, and (e) benefits of the study.